The evolution of fiqh in the digital era: Challenges and adaptations in islamic jurisprudence - Prayogi, Arditya; Nasrullah, Riki; Singgih Setiawan (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The rapid advancement of digital technology has significantly transformed various aspects of human life, including Islamic jurisprudence (fiqh). As a discipline that provides legal guidance for Muslims, fiqh must continuously adapt to new challenges brought by digitalization. This study examines how fiqh evolves in response to contemporary digital developments and their implications for Islamic law and daily Muslim practices. Methods: This research employs a qualitative descriptive method, utilizing primary and secondary sources from print and electronic media related to fiqh in the digital era. Data were collected through literature review, analyzed using thematic categorization, and validated through triangulation to ensure reliability and contextual accuracy. Findings: The study reveals that fiqh remains dynamic and flexible in addressing modern challenges such as online transactions, artificial intelligence in financial decision-making, and ethical concerns in social media usage. While technology provides convenience, it also raises new fiqh-related questions requiring scholarly ijtihad. Additionally, the digital era has influenced the process of issuing and disseminating fatwas, necessitating innovative approaches to maintain their validity and authority. Conclusion: Fiqh in the digital era must balance technological advancements with core Islamic principles. The role of scholars and fatwa institutions is crucial in ensuring that digital transformation aligns with sharia guidelines. Continuous adaptation is essential to preserve the relevance of Islamic law in modern society. Novelty/Originality of this article: This study uniquely highlights how fiqh interacts with emerging digital challenges, emphasizing its importance in guiding Muslims to integrate technological advancements within Islamic ethical and legal frameworks.